Clinical relevance linked to echocardiography diagnosis in Bland, White and Garland syndrome - Almira, Mariela Céspedes; González Morejón, Adel Eladio; Ricardo, Giselle Serrano; González Rodríguez, Tania Rosa (Journal of Cardiology and Cardiovascular Medicine, 2020)
Introduction: Bland, White and Garland syndrome is a coronary anomaly with high mortality without treatment. Its clinical presentation is varied which makes epidemiological documentation difficult. Echocardiography is a useful non-invasive tool for diagnosis. Objective: To determine the echocardiographic variables that lead to the diagnosis of Bland, White and Garland syndrome and their clinical relevance. Material: Observational, prospective and cross-sectional study in 31 patients of the “William Soler” Pediatric Cardiocenter, from 2005 to 2018. To check the association of echocardiographic variables with the diagnosis of Bland, White and Garland syndrome, an effectiveness study was carried out that included the analysis of the incidence of echocardiographic variables that lead to the diagnosis of this entity. The clinical relevance was estimated according to the minimum importance limit. The statistical validation of the research results adopted a significance level of less than 5% (p < 0.05). Results: The variables that facilitate the echocardiographic diagnosis of Bland, White and Garland syndrome were the echocardiographic visualization of the anomalous connection and the reversed flow in the anomalous left coronary artery. These echocardiographic measures have clinical relevance according to the quantification of risk estimators (incidence) the echocardiographic visualization of the anomalous connection, RR 39.00 and the reversed flow in the anomalous coronary artery, RR 26.31. LIM´s calculation value amounted to 6.31 and coincided with the risk estimators (incidence). Conclusion: The echocardiographic visualization of the anomalous origin of the left coronary artery from the pulmonary arterial trunk and the detection of the local intracoronary reversed flow instituted as factors to be considered for the effective diagnosis of the disease. The documentation of the diagnostic aspects of the syndrome through echocardiography contains high statistical value and clinical relevance.